Membentuk Peserta Didik Menggunakan Bahasa yang Tidak Menyinggung - Enjelina Enjelina; Sriwati Sihombing; Putra Jungjungan Rajagukguk; Hisardo Sitorus (Pusat riset dan Inovasi Nasional, 2025)
Indonesia, as a multicultural nation, demands that Christian Religious Education (PAK) practices focus not only on doctrinal teaching but also on character development for students, enabling them to live within cultural, ethnic, and religious diversity. Language is a crucial element in realizing inclusive education, as the use of impolite or offensive language can trigger prejudice, intolerance, and even bullying, as seen in the forced hijab case in Bantul. This study uses a literature review method to examine the role of language, politeness, and communication strategies in developing students who value pluralism and multiculturalism. The discussion demonstrates that politeness is the foundation of character development and reflects a person's moral values. Through strategies such as integrating Christian values ​​into the curriculum, inclusive teaching methods, creating a school environment that supports diversity, and a holistic communication approach, Christian Religious Education can be a means of transformation that fosters tolerance and harmony. The results confirm that the use of polite and non-offensive language is a key aspect in developing students with character, who are inclusive, and capable of becoming agents of peace in a pluralistic society.